The Utility of Systemic Inflammatory Markers to Predict Emergent Cerclage - Duymus, Ayse Ceren; Bozbay , Nizamettin; Agakishieva , Leyla; Pekin , Aybike; Orgul, Gokcen (Gynecology Obstetrics & Reproductive Medicine, 2025)
OBJECTIVE: The inflammatory markers examined in this study have been previously associated with adverse neonatal outcomes in numerous studies, raising the question of whether cervical insufficiency is also linked to these markers. To address this issue, the present study was designed to identify a simple, cost-effective biochemical predictor of unpredictable cervical insufficiency. STUDY DESIGN: This retrospective study included a total of 34 patients who underwent emergency cerclage procedures at the clinic between 2018 and 2024. The control group consisted of pregnant women randomly selected from the patient population who sought care at the outpatient clinic for routine pregnancy check-ups. They were followed throughout their pregnancies at our hospital and delivered at term without complications. The systemic immune-inflammation index, systemic inflammation response index, neutrophil-lymphocyte ratio, lymphocyte-to-monocyte ratio, and platelet-to-lymphocyte ratio were calculated from the complete blood counts of both groups during the first and second trimesters. Group comparisons and receiver operating characteristic analyses were performed. RESULTS: The lymphocyte-to-monocyte ratio in patients who underwent emergency cerclage was significantly higher than that observed in healthy pregnant women during both the first and second trimester complete blood counts. CONCLUSION: Lymphocyte-to-monocyte ratio may be a promising and cost-effective marker for predicting CI requiring EC. Further prospective studies with larger cohorts are warranted.